Hubungan Lama Pemakaian Kontrasepsi Suntik 3 Bulan Dengan Perubahan Peningkatan Berat Badan Pada Akseptor KB Suntik 3 Bulan Di Puskesmas Terawan - Nurul Maulida Fatmawati; Sri Wahyuni; Uswatun Kasanah (Jurnal Medika Nusantara, 2023)
Injection contraception is contraception that is given by injection intramuscularly in the buttocks muscle area. According to WHO (2014), the use of DMPA injection contraception is 57.4% of the total contraceptive users in the world. Indonesia (2014) amounted to 49.67% of the total contraceptive users in Indonesia. From the results of a preliminary study conducted by researchers at the Terawan Health Center, the number of DMPA injectable birth control acceptors who experienced changes in body weight in 2022 was 45 acceptors. This study aims to determine the relationship between the duration of 3-month injection contraception use and changes in body weight in 3-month injection contraceptive acceptors at the Terawan Health Center. This study uses an analytical method with a retrospective approach. Which was carried out at the Terawan Health Center in 2023 with a total sample of 45 people using a purposive sampling technique from secondary data. The independent variable is duration of use of DMPA injection contraception and the dependent variable is the incidence of changes in body weight. It can be concluded from the results of bivariate analysis using the chi square test of 45 samples, there is a positive and significant relationship between the duration of 3-month injection contraceptive use and changes in weight gain in family planning acceptors with a P value: 0.002 (<0.05).